Meningkatkan Kemampuan Berpikir Kritis, Kerja Sama, Dan Hasil Belajar Siswa Menggunakan Model Barikit Pada Muatan Pkn Kelas IV SDN Telawang 4: Studi Tindakan Kelas pada Siswa Kelas IV SDN Telawang 4 Tahun Ajaran 2024/2025 - Nursyifa .; A. Suriansyah; R. Purwanti (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
This study aims to improve student activity, critical thinking skills, collaboration, and learning outcomes in Civics (PPKn) learning through the implementation of the BARIKIT learning model. The problem identified in this research is the low level of student engagement, critical thinking ability, collaboration, and academic achievement in PPKn content. The root causes include low student interest in learning, limited reasoning skills, monotonous and less interactive learning activities, and the lack of engaging learning facilities. Additionally, students often struggle to express their opinions during lessons. This Classroom Action Research was conducted over four meetings with 20 fourth-grade students at SDN Telawang 4 in the 2024/2025 academic year. Data were collected through observation and tests, then analyzed using descriptive analysis and cross-tabulation. The results showed a significant improvement in teacher activity (from a score of 29 to 35), student activity (from 45% to 90%), critical thinking (from 25% to 90%), collaboration (from 45% to 90%), and student learning mastery (from 35% to 95%). These findings indicate that the BARIKIT model is effective in enhancing the quality of Civics instruction. Its consistent implementation successfully improves learning activities, social and cognitive interaction skills, as well as student achievement in PPKn content. The model can serve as an alternative interactive teaching method in primary schools.